2020
DOI: 10.1109/tnse.2019.2952369
|View full text |Cite
|
Sign up to set email alerts
|

On New Approaches of Maximum Weighted Target Coverage and Sensor Connectivity: Hardness and Approximation

Abstract: In mobile wireless sensor networks (MWSNs), each sensor has the ability not only to sense and transmit data but also to move to some specific location. Because the movement of sensors consumes much more power than that in sensing and communication, the problem of scheduling mobile sensors to cover all targets and maintain network connectivity such that the total movement distance of mobile sensors is minimized has received a great deal of attention. However, in reality, due to a limited budget or numerous targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 45 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Moreover, it also studied the water use efficiency under different irrigation methods, and then concluded that a reasonable and thorough irrigation method is much better than traditional farming methods. Jia et al (2017) and Nguyen et al (2020) conducted experimental research on rice irrigation areas and found that traditional irrigation methods caused a lot of waste of water resources, and 50% of the water volume was field leakage. Karbasi (2018) proposed four aspects: sustainable development, ecological quality, consideration of the impact of macro-scale systems and planning of natural and social systems.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it also studied the water use efficiency under different irrigation methods, and then concluded that a reasonable and thorough irrigation method is much better than traditional farming methods. Jia et al (2017) and Nguyen et al (2020) conducted experimental research on rice irrigation areas and found that traditional irrigation methods caused a lot of waste of water resources, and 50% of the water volume was field leakage. Karbasi (2018) proposed four aspects: sustainable development, ecological quality, consideration of the impact of macro-scale systems and planning of natural and social systems.…”
Section: Related Workmentioning
confidence: 99%
“…Target coverage is also an important topic. Most target coverage problems were NP-hard problem, optimization algorithms were applied to them including evolutionary algorithms [ 11 , 29 , 30 , 31 , 32 ] and combinatiorial algorithms [ 17 , 33 , 34 , 35 , 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…In our paper, we study the MTCLM problem to cover maximum number of targets with sensors with limited mobility, which is different from the Maximum Weighted Target Coverage problem in Reference [ 36 ] because the mobility is limited. And the maximumcoverage-based algorithm is not suitable anymore.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Coverage is one of the most important applications of wireless sensor networks (WSN), where sensors are placed on an area of interest to monitor the environment and detect extraordinary activities. There have been many studies on this topic across different subject areas including discrete points [ 1 , 2 ], 2-dimensional surfaces [ 3 ], 3-dimensional surfaces [ 4 ], 3-dimensional spaces, fences [ 5 , 6 ], and so on. Based on sensors’ characteristic, special factors should be considered, such as energy efficiency, maintaining connectivity, and so on [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%